Physiological response of soybean under water stress in two "cerrado" soils - Silva, José Eurípedes da; Resck, Dimas Vital S. (Pesquisa Agropecuaria Brasileira, 2014)
The physiological responses of soybean with different degrees of water stress was observed in both clay DRL (Dark Red Latosol) and sandy clay RYL (Red Yellow Latosol) cerrado soils, through the observation of RWC (Relative Water Content), Ψwf (Leaf Water Potential) and rs (Stomatal Diffusive Resistance), as the stress developed. The soil water content for the same degree of plant water stress was different between the soils but the values of RWC, Ψwf and rs measured in plants, show that the stomats closed at 10 bars of leaf water potential in both soils, corresponding to 25.5 e 19% of soil water content for DRL and RYL soils, respectively. From the data, a scale with four stress stages related to moisture content of soil was made. The plant wilting ranged from 24 to 21% and from 14.5 to 12% of moisture content in DRL and RYL, respectively. The lower limit of each range of DRL and RYL soils respectively corresponds to RWC of 35%, Ψwf of 23-25 bars and rs of 34 s/cm, measured in plants in that point.